Strontium isotope correlation of the basal Maastrichtian Stage in Antarctica to the European and US biostratigraphic schemes - Crame, JA; McArthur, JM; Pirrie, D; Riding, JB (GEOLOGICAL SOC PUBL HOUSE, 1999)
New Sr-87/Sr-86 dating allows the correlation of a marker horizon within the prolific Late Cretaceous Gunnarites antarcticus faunal assemblage of the Cape Lamb Member, Snow Hill Island Formation, Vega Island, Antarctica with reference sections in Europe and the USA. This horizon is between 81.5 and 96.5 m above the base of the G. antarcticus assemblage. Replicate analysis of six macrofossils from within it yielded a mean value for Sr-87/Sr-86 of 0.707 735 9 +/- 0.000 004 3 (+/- 2 s.e., n=17). This ratio in turn yields a numerical age of 71.0 +/- 0.2 Ma when compared to the standard Sr-87/Sr-86 reference curve for the latest Cretaceous, for which the Campanian-Maastrichtian boundary is placed at 71.3 +/- 0.5 Ma. The value of 0.707 735 9 +/- 0.000 004 3 correlates to a level in the Belemnella lanceolata belemnite Zone of the Chalk of northwestern Germany that is 2.5 +/- 5 m beneath the base of the overlying B. pseudobtusa Zone land 7.5 m above the Campanian-Maastrichtian belemnite boundary, and to an interval within the ammonite zonation of the US Western Interior that spans the early Maastrichrian Baculites baculus and B. eliasi zones, but with a most likely level within the B. eliasi Zone. An earliest Maastrichtian age is thereby determined for the Antarctic horizon, and indeed for the entire G. antarcticus assemblage. Gunnarites, sensu lato, is an important ammonite marker for the base of the Maastrichtian throughout the southern high-latitude regions, and the associated large heteromorph ammonite Diplomoceras may comprise a macrofossil link back to the Maastrichtian type sections.